Exploring "Flow" in young Chinese EFL learners' online English learning activities. (February 2021) - Liu, Honggang; Song, Xueyan
Abstract: Flow has been widely researched in the fields of psychology, educational psychology and so on ever since it was first proposed by Csikszentmihalyi (1975), and in recent years it has been further explored in relation to the emotions related to online course learning (Shin, 2006) and digital game playing (Killi, 2005). However, it has less been applied in the field of foreign language education, especially in the era of digital language learning. To fill this gap, we focused on the flow experience of 235 Chinese junior high school students during online English learning using English Fun Dubbing as the software medium. Three stages of flow (antecedents, experience and consequences) were measured to investigate: (1) students' experience during the dubbing task, and (2) differences between students with high and low dubbing work scores. Quantitative data analysis followed by interviews showed the students had a moderately-high flow experience among the three flow stages. The flow experience was similar for both student groups, but there were significant variations in the flow antecedents (skill, challenge, and clear goals). These findings have implications for designing and implementing young learners' English teaching and learning activities.